Implications Of Development Of Computer And Internet Technology For School Counselors - Rahayu Sri Utami; Yusniar; Intan Permata Sari; Aliazer Hutapea (Akademi Manajemen Informatika dan Komputer Widya Loka Medan, 2022)
The growth of computer and internet technology has their implication toward guidance and counseling field. School Counselors as subjects those who directly affiliated with the impact must anticipate with knowledge and skills of using of computer and internet technology. Skills and knowledge masteries are extremely needed by school counselors so that they could employ technological base guidance and counseling services. The real fact occurs in schools indicate that many school counselors who are stutter about technology. Therefore, there are two matters which presented in this article, they are: 1) why school counselors are stutter about technology 2) what proposed solution to overcome that case?